2022
DOI: 10.31635/ccschem.021.202101120
|View full text |Cite
|
Sign up to set email alerts
|

Red-Emissive Organic Room-Temperature Phosphorescence Material for Time-Resolved Luminescence Bioimaging

Abstract: Organic room temperature phosphorescence (RTP) materials have been used in high resolution imaging.However, the development of long-wavelength emission RTP materials in aqueous solution are still challenging.In this work, we developed red emissive RTP materials via integration of ring-fusing effect and host-guest interaction. The fused ring guest molecule showed low triplet state for long-wavelength emission, and the host molecule can bridge the huge gap between the triplet and singlet of guest molecules for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 66 publications
0
37
0
Order By: Relevance
“…For the guest‐host system TPACN/TPABr , orange‐red RTP (maximum at 600 nm) was observed with a quantum yield of up to 7.2 % and a lifetime of 184 ms (Table 1). Given that the red‐organic RTP emission for the TPACN/TPABr system was generally suppressed owing to the energy‐gap law, the non‐radiative transition was not inhibited satisfactorily [4b] . However, the non‐radiative rate constant of phosphorescence ( k nr P ) in the case of TPABr is considerably low.…”
Section: Resultsmentioning
confidence: 99%
“…For the guest‐host system TPACN/TPABr , orange‐red RTP (maximum at 600 nm) was observed with a quantum yield of up to 7.2 % and a lifetime of 184 ms (Table 1). Given that the red‐organic RTP emission for the TPACN/TPABr system was generally suppressed owing to the energy‐gap law, the non‐radiative transition was not inhibited satisfactorily [4b] . However, the non‐radiative rate constant of phosphorescence ( k nr P ) in the case of TPABr is considerably low.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the absence of a traditional fluorophore, some natural polymers, such as rice, starch, and cellulose generally exhibited bright fluorescence upon aggregation due to heteroatom-rich backbones. This unique phenomenon was named clusterization-triggered emission (CTE). The CTE polymers without large π-conjugated backbones can have some unique advantages, including outstanding solubility, good optoelectronic, facile preparation, and environmental friendliness. , Recently, some polymers developed by MCPs also exhibited the CTE phenomenon due to the introduction of heteroatoms and unsaturated units. , However, only limited studies on CTE in phosphorescence have been reported due to the unstable triplet states for phosphorescence emission. Triplet state excitons generated radiative transitions for a longer phosphorescence emission duration of seconds to hours after the cease of irradiation, which has attracted extensive attention due to its broad application range from lighting and optical recording to chemical sensing and bioimaging. The development of new polymeric phosphors with controllable aggregated structures that exhibit the desired phosphorescence properties is still a challenging task. Systematic investigation of the tunable triplet-excited states of polymeric materials will facilitate to develop the room-temperature phosphorescence (RTP) materials with long emission wavelength that were potentially used as deep penetration bioimaging materials. …”
Section: Introductionmentioning
confidence: 99%
“…Notably, the prerequisite to the formation of twisted ICT relies on active molecular rotations, whose nonradiative decay may be employed for the development of advanced biological/biomedical photothermal agents . Meanwhile, intramolecular D–A interactions can narrow the energy gap between the lowest singlet and triplet state (Δ E ST ) to enhance the intersystem crossing (ISC) ability of excitons. This is also considered as a nonradiative relaxation process from excited singlet state to highly sensitive triplet state, which quenches the fluorescence . Recently, Crespo-Otero et al showed through an advanced computational study that for effective enhancement of solid-state luminescence, the population of triplet states should be also hampered .…”
Section: Introductionmentioning
confidence: 99%
“…Although ISC is a pathway competitive to fluorescence, it is a prerequisite for the generation of triplet excitons . Efficient modulation of excited-state energy to populate the triplet excited state can be used in photosensitizers to produce reactive oxygen species (for photodynamic therapy) and to generate room temperature phosphorescence (RTP) materials that can be widely applied in fields including OLEDs, anticounterfeiting, ,, and bioimaging. , …”
Section: Introductionmentioning
confidence: 99%